Doing sociology in India : genealogies, locations, and practices - Patel, Sujata (New Delhi : Oxford University Press, 2016)
"This volume on the history of sociology in India locates scholars, scholarship, theories, perspectives, and practices of the discipline in different cities and regions of the country over a century. It argues that this history is enmeshed in political projects of constructing a society, which took place as a result of colonialism and dominant nationalism. The book affirms the existence of both strong and weak traditions of scholarship in India, and underscores three processes that have aided this development at various points of time: reflexive interrogation of received scholarship; probing ideal types of theories within the classroom; and questioning existing debates on society and its language by publics."--Page 4 of cover.
Ruminating on sociological traditions in India / Sujata Patel -- Sociology : the genealogy of the discipline in Bombay / Manorama Savur -- The public culture of sociology in Calcutta / Anjan Ghosh -- Searching for bedrock : contending with the Lucknow School and its legacy / Sasheej Hegde -- Social anthropology or Marxist sociology? : Assessing the contesting sociological visions of M.N. Srinivas and A.R. Desai / Sujata Patel -- Of centres and peripheries : sociology in Goa / Alito Siqueira and Manish Thakur -- Legacy and rigour : the Bombay School of sociology and its impact in universities in Maharashtra / D.N. Dhanagare -- Looking back : the practice of sociology in CSSS/JNU / Maitrayee Chaudhuri -- Sociology in Karnataka : the formation and decline of a discipline / N. Jayaram -- Exorcising the fear of identity : interrogating the "language question" in sociology and sociological language / Sharmila Rege -- Knowledge production and transmission : learning sociology at the undergraduate level / Edward A. Rodrigues -- Colonial anthropology, law, and Adivasi struggles : the case of Jharkhand / Carol Upadhya -- Scripting sociology of science : between knowledge and democracy in India / Shiv Visvanathan.
Originally published: 2011.
Minimal Level Cataloging Plus.
Includes index.
Keywords: SOCIOLOGY -- INDIA -- History; INDIA; INDIA--LOCATION; GENEALOGIES; PRACTICES